Brand Image and Pricing as Determinants of Consumer Purchase Decisions - Yayu Kusdiana; Nanda Suryadi; Mazzlida Mat Deli (Yayasan Pendidikan Islam Al-Matani, 2025)
This study investigates the impact of Brand Image and Price on Purchase Decisions at Takoyaki Janda, Raun–Raun Food Park, Pekanbaru, using a sample of 67 respondents. Data were analyzed via multiple linear regression, hypothesis testing, and determination coefficient calculation using SPSS 25. Findings reveal that both Brand Image and Price exert significant partial effects on purchase decisions, as well as a significant combined effect. The Adjusted R² of 0.747 indicates that these variables account for 74.7% of the variance in purchase decisions, with the remaining 25.3% explained by factors beyond the scope of this study.